2016
DOI: 10.1002/ange.201604812
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Silylamine from N2 and a Silane: Mediated by a Tridentate Phosphine Molybdenum Fragment

Abstract: Ah omogeneous system which is able to yield silylamine from N 2 and bis(silane) in one pot is reported. Mechanistically a{ (triphosphine)molybdenum(I)} fragment, generated in situ, splits N 2 into the corresponding nitrido complex at room temperature.T hen, functionalization of the molybdenum nitrido is achieved by double Si À Ha ddition under mild reaction conditions.M oreover,t he bis(silyl)amine product is decoordinated from the metal center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 65 publications
2
28
0
Order By: Relevance
“…[4] Thed irect synthesis of compounds other than NH 3 from N 2 remains af ormidable challenge.C atalytic protocols are only known for trisilylamine. [5] Nitriles, [6][7][8] isocyanates, [9] silylamines, [10,11] and borylamines [12] have been synthesized within stoichiometric,c yclic reaction sequences,w hich allow for evaluating strategies to offset the extremely strong NNbond (225 kcal mol À1 ), enable EÀN(E= C, Si, B) bond formation and deliver six reduction equivalents.A ll reported "synthetic cycles" proceed through initial N 2 cleavage into nitride complexes. Subsequent nitrogen transfer typically requires strong electrophiles like alkyl triflates.T he thermochemistry of N 2 splitting must therefore be tuned to avoid nitride overstabilization and enable functionalization with reagents that are more compatible with reductive conditions.…”
mentioning
confidence: 99%
“…[4] Thed irect synthesis of compounds other than NH 3 from N 2 remains af ormidable challenge.C atalytic protocols are only known for trisilylamine. [5] Nitriles, [6][7][8] isocyanates, [9] silylamines, [10,11] and borylamines [12] have been synthesized within stoichiometric,c yclic reaction sequences,w hich allow for evaluating strategies to offset the extremely strong NNbond (225 kcal mol À1 ), enable EÀN(E= C, Si, B) bond formation and deliver six reduction equivalents.A ll reported "synthetic cycles" proceed through initial N 2 cleavage into nitride complexes. Subsequent nitrogen transfer typically requires strong electrophiles like alkyl triflates.T he thermochemistry of N 2 splitting must therefore be tuned to avoid nitride overstabilization and enable functionalization with reagents that are more compatible with reductive conditions.…”
mentioning
confidence: 99%
“…However,the use of strong electrophiles and reducing agents efficiently leads to electrophile homocoupling as ac ompetitive reaction. While silylamine formation was achieved by the double SiÀHb ond functionalization of the MoNi ntermediate, [10] this process is limited to its intramolecular version, and requires the use of bis-silane in excess and prolonged heating. [6] In turn, very large activation energy is required to split N 2 at the surface of the heterogeneous catalyst prior to functionalization.…”
Section: In the Memory Of Pascal Le Flochmentioning
confidence: 99%
“…[2] Most impressively,s everal Mo, [3] Fe, [4] and Co [5] complexes have proven efficient catalysts for NH 3 and N(SiMe 3 ) 3 synthesis,with TON (turn over number) up to circa 415 and 220, respectively. While silylamine formation was achieved by the double SiÀHb ond functionalization of the MoNi ntermediate, [10] this process is limited to its intramolecular version, and requires the use of bis-silane in excess and prolonged heating. On the other hand, the Haber-Bosch uses H 2 as both the N 2 functionalizing and reducing species,t hereby potentially avoiding any side reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Unfortunately,both strategies rely on the use of strong electrophiles (acylc hloride/silyltriflate and ethyl triflate,r espectively) which are incompatible with the N 2 reduction step.With the ultimate goal of developing catalytic N 2 fixation, the functionalizing reagent needs to react selectively with the high-valent nitrido complex rather than with the reduced metal center.W eh ave recently shown that Si À Hb onds of silanes react selectively toward a( PP 2 )Mo IVnitrido complex and not with the corresponding Mo I fragment. While silylamine formation was achieved by the double SiÀHb ond functionalization of the MoNi ntermediate, [10] this process is limited to its intramolecular version, and requires the use of bis-silane in excess and prolonged heating. Fort he present study,w ereasoned that the strength of N À B bond would be astrong driving force and that the Lewis acid character of boranes could provide alow energy pathway for MoNfunctionalization.…”
mentioning
confidence: 99%